THE PKSN STRATEGY (NATIONAL STRATEGIC ACTIVITIES CENTER) BASED ON GRAND DESIGN OF STATE BORDERS MANAGEMENT - Johnson, Posma Sariguna Johnson; L.Tobing, Suzanna Josephine; Heatubun, Adolf Bastian; Lumbantoruan, Rutman (Fundamental Management Journal, 2018)
Central and local governments face various obstacles in realizing National Strategic Activities Center (PKSN) development. This paper aims to review it, by conducting normative studies. We study various literature and regulations issued by the government. Many of the problems in the field that must be considered. They are the absence of concrete minimum requirements related to border services within the city PKSN, the absence of incentives / disincentives to development programs "to-border" in PKSN , not yet the strict regulation on land management and spatial layout of PKSN, and the lack of Government support in terms of preparation of border city infrastructure, causing low attractiveness.Keywords: National Strategic Activities Center (PKSN), State Border Area, Spatial Plan (RTRW)